Sensitivity and specificity of rRT-PCR, histopathology, and immunohistochemistry for the detection of rift valley fever virus in naturally-infected cattle and sheep - Clift, Sarah J. (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2014.